Poverty Impacts of the Volume-Based Special Safeguard Mechanism - Ivanic, Maros; Martin, Will (World Bank Group, Washington, DC, 2014)
The volume-based Special Safeguard Mechanism was proposed as essential for small, poor farmers and became the proximate cause of the collapse of the Doha Agenda negotiations in 2008. But is it helpful for these farmers, given that it is likely to be applied when farm output is depressed and many poor farmers in developing countries need to buy food? Stochastic simulations for 31 countries suggest that use of this safeguard in line with the proposed World Trade Organization rules would raise the world poverty headcount by an average of 24 million. The adverse poverty impact of the duty is larger when the quantity safeguard is triggered than it would be in other years, because lower farm output levels reduce or reverse the benefits to poor farm households from higher prices.